PERAN DAN UPAYA PEMERINTAH DALAM PEMBERANTASAN PERJUDIAN ONLINE DI INDONESIA - Angelia, Rina Rahma Ornella; Desmon, Andi; Syofiyani, Melsi (Ensiklopedia of Journal, 2025)
Abstract: Gambling is one of the phenomena that is currently developing in Indonesian society. The government as a law enforcer has a very important role in eradicating gambling, considering the negative impacts caused by gambling. The negative impacts of gambling include addiction, job loss, family breakdown, debt, and legal sanctions. The role and efforts of the government in eradicating online gambling are by making regulations (rules) and licenses for the provisions of regulations related to gambling, conducting international cooperation with other countries related to gambling, and collaborating with the technology industry. The method used in this writing is through a normative legal approach as the main approach to existing laws and regulations. The data used are in the form of primary data and secondary data which are then analyzed qualitatively and presented in descriptive form. The regulations used are in the form of provisions governing Electronic Information and Transactions, Regulations related to the Implementation of Gambling Control and regulations on arts organizations.Keywords: Online gambling, Eradication, Government efforts, Role of Government, Law enforcement.